2005
DOI: 10.1002/chem.200500762
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Iridium‐Catalyzed Asymmetric Hydrogenation of Dienes

Abstract: Hydrogenation of 2,3-diphenylbutadiene (1) with the chiral carbene-oxazoline-iridium complex C has been studied by means of a combined experimental and computational approach. A detailed kinetic profile of the reaction was obtained with respect to consumption of the substrate and formation of the intermediate half-reduction products, 2,3-diphenylbut-1-ene (2) and the final product, 2,3-diphenylbutane (3). The data generated from these analyses, and from NMR experiments, revealed several facets of the reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…[18,[22][23][24][25] Detailed theoretical studies from these laboratories have led us to conclude that hydrogenation of stilbene and styrene derivatives by catalyst 1 proceeds by a cycle involving a dihydride-dihydrogen iridium complex and cycling between Ir III and Ir V oxidation states. [26] These observations were broadly similar to those calculated by Brandt, Andersson and coworkers for a simplified phosphine-oxazoline iridium complex mediating hydrogenation of ethene.…”
Section: Wwwchemeurjorgmentioning
confidence: 96%
See 1 more Smart Citation
“…[18,[22][23][24][25] Detailed theoretical studies from these laboratories have led us to conclude that hydrogenation of stilbene and styrene derivatives by catalyst 1 proceeds by a cycle involving a dihydride-dihydrogen iridium complex and cycling between Ir III and Ir V oxidation states. [26] These observations were broadly similar to those calculated by Brandt, Andersson and coworkers for a simplified phosphine-oxazoline iridium complex mediating hydrogenation of ethene.…”
Section: Wwwchemeurjorgmentioning
confidence: 96%
“…In response, we have begun to study dienes and polyenes. [17][18][19] Then, very recently, Pfaltz et al reported reduction of a 1,5,9-triene to give (R,R,R)-toScheme 1. a) Internal deoxypolypropionate chirons and b) the asymmetric hydrogenation approaches to these chirons that are investigated here. P = protecting group, FG = CH 2 OH, CH 2 OR, or CO 2 R. Scheme 2.…”
Section: Introductionmentioning
confidence: 98%
“…A chiral carbene-oxazoline ligand L5 is also useful for this purpose. 59 The mechanism of this reaction is to be elucidated by experimental [60][61][62][63] and theoretical 64,65 studies. Chiral titanocene catalysts also show high enantioselectivity for hydrogenation of simple olefins.…”
Section: Hydrogenation Of Simple Olefins With Iridium Catalystsmentioning
confidence: 99%
“…Electronic effects drive the alkene substrate trans to the NHC, enabling steric effects (mainly adamantane/alkene interaction) to efficiently control enantioface discrimination. [170] The application of 101 to the hydrogenation of more complex functionalised dienes has also been described, [171,172] whilst a pyrimidine analogue was recently described. [173] In direct line with the work of Burgess, Pfaltz has reported a library approach to 2-and 4-oxazoline-NHC cationic Ir I complexes (Scheme 21).…”
Section: Asymmetric Olefin Hydrogenation (Rh Ir)mentioning
confidence: 97%